CALON TUNGGAL DAN KOMUNIKASI POLITIK PARTAI DALAM PILKADA SERENTAK 2015 DI INDONESIA - Lestari Nurhajati (Avant Garde, 2016)
The simultaneously local elections in Indonesia from the beginning gave rise to various views of the pro and cons. The situation is not immediately stopped, although the regulations of simultaneous local elections already set in by Law of the Republic of Indonesia No. 1 2015 Article 3. As a result of a legal product between parliament and government, and has been signed by the president Indonesia, Joko Widodo on February 2, 2015, but the practice of political parties do not wholeheartedly run of the Act. This is evident from the attitudes and intentions of political communication that is displayed by most political parties. The purpose of this study is to see how framing the news carried by online media in addressing the political communication political parties on the issue of a single candidate in the elections of 2015. This study uses the analysis of framing news online media in detik.com., liputan6.com and kompas.com. Situation single candidate various areas is one indicator of how political communication gap occurs. The issue of transaction politics, the failure of regeneration, and the loss of sportsmanship in politics, be three reasons most easily observed in the reporting of political parties and a single candidate in Indonesia.